Perioperative immune function and pain control may underlie early hospital readmission and 90 day mortality following lung cancer resection: A prospective cohort study of 932 patients. Issue 5 (May 2019) - Oswald, Nicola; Halle-Smith, James; Kerr, Amy; Webb, Joanne; Agostini, Paula; Bishay, Ehab; Kalkat, Maninder; Steyn, Richard; Naidu, Babu
Abstract: Background: Mortality following lung cancer resection has been shown to double between 30 and 90 days and readmission following surgery is associated with an increased risk of mortality. The aim of this study was to describe the causes of readmission and mortality and enable the identification of potentially modifiable factors associated with these events. Methods: Prospective cohort study at a United Kingdom tertiary referral centre conducted over 55 months. Binary logistic regression was used to identify factors associated with death within 90 days of surgery. Results: The 30 day and 90 day mortality rates were 1.4% and 3.3% respectively. The most common causes of death were pneumonia, lung cancer and Acute Respiratory Distress Syndrome/Multi Organ Failure. Potentially modifiable risk factors for death identified were: Postoperative pulmonary complications (Odds ratio 6.1), preoperative lymphocyte count (OR 0.25), readmission within 30 days (OR 4.2) and type of postoperative analgesia (OR for intrathecal morphine 4.8). The most common causes of readmission were pneumonia, shortness of breath and pain. Conclusions: Postoperative mortality is not simply due to fixed factors; the impacts of age, gender and surgical procedure on postoperative survival are reduced when the postoperative course of recovery is examined. Perioperative immune function, as portrayed by the occurrence of infection and lower lymphocyte count in the immediate perioperative period, and pain control method are strongly associated with 90 day mortality; further studies in these fields are indicated as are studies of psychological factors in recovery. Clinical registration number: ISRCTN00061628.